1995
DOI: 10.1038/377239a0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in mice lacking the gene for endothelial nitric oxide synthase

Abstract: Nitric oxide (NO), a potent vasodilator produced by endothelial cells, is thought to be the endothelium-dependent relaxing factor (EDRF) which mediates vascular relaxation in response to acetylcholine, bradykinin and substance P in many vascular beds. NO has been implicated in the regulation of blood pressure and regional blood flow, and also affects vascular smooth-muscle proliferation and inhibits platelet aggregation and leukocyte adhesion. Abnormalities in endothelial production of NO occur in atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

65
1,222
9
23

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,913 publications
(1,319 citation statements)
references
References 24 publications
65
1,222
9
23
Order By: Relevance
“…11,[31][32][33][34][35] ASSESSMENT OF ENDOTHELIAL FUNCTION In experimental studies, methods for assessment of endothelial function have been established by using a ring experiment protocol, endothelial functional alteration in expression of transcriptional factors and genes and genetic ablation of endothelial NO synthase (eNOS) in animal models. 36,37 It is clinically important to estimate the degree of endothelial dysfunction. Several methods have been used to assess endothelial function in humans.…”
Section: Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[31][32][33][34][35] ASSESSMENT OF ENDOTHELIAL FUNCTION In experimental studies, methods for assessment of endothelial function have been established by using a ring experiment protocol, endothelial functional alteration in expression of transcriptional factors and genes and genetic ablation of endothelial NO synthase (eNOS) in animal models. 36,37 It is clinically important to estimate the degree of endothelial dysfunction. Several methods have been used to assess endothelial function in humans.…”
Section: Endothelial Functionmentioning
confidence: 99%
“…36 Systolic blood pressure was elevated by approximately 30 mm Hg in eNOS knockout mice compared with that in wild-type mice. 37 In hypertensive patients also, endothelium-dependent vascular relaxation in coronary, forearm and renal arteries was found to be impaired, and endothelial dysfunction, which is involved in the development of atherosclerosis, was found to increase the risk of cardiovascular and cerebrovascular diseases. [9][10][11][12][13][14][15]27,35 As Panza et al 9 reported for the first time in 1990 that the dose-response curve obtained by acetylcholine in patients with hypertension was smaller than the curve in normal controls and that the dose-response curves obtained by sodium nitropreside were similar in the two groups, suggesting that endothelial function, but not smooth muscle function, is selectively impaired in patients with hypertension, a large number of studies have shown that hypertension is associated with endothelial dysfunction.…”
Section: Endothelial Dysfunction and Hypertensionmentioning
confidence: 99%
“…Knockout mice deficient in eNOS had hypertension as adults. 2 In contrast, induction of eNOS cDNA in mice reduced BP. 3 As the genomic sequence of eNOS is highly polymorphic, it is of added interest to these findings to confirm which variant(s) at eNOS might have a functional potential to affect the final bioavailability of eNOS, and thus the development of hypertension.…”
mentioning
confidence: 99%
“…Evidence is mounting suggesting that enhanced production or bioavailability of the enzyme eNOS that synthesizes NO in endothelial cells may lead to the constitutive release of NO, which exerts vasoprotective effects in blood pressure (BP) regulation. 1,2 The eNOS spans 21 kb with 26 exons on chromosome 7q35-36. The candidacy for eNOS in the development of hypertension has a strong biological basis.…”
mentioning
confidence: 99%
“…inhibiting vascular smooth muscle contraction) [5]. Indeed, it has been observed in an animal model that the disruption of NOS3 gene led to hypertension, while in humans the inhibition of NOS3 elevated BP [5,6].…”
Section: Introductionmentioning
confidence: 99%